Development of Food Pattern Recommendations for Infants and Toddlers 6–24 Months of Age to Support the Dietary Guidelines for Americans, 2020–2025. Issue 10 (30th June 2021) - Dewey, Kathryn G; Pannucci, TusaRebecca; Casavale, Kellie O; Davis, Teresa A; Donovan, Sharon M; Kleinman, Ronald E; Taveras, Elsie M; Bailey, Regan L; Novotny, Rachel; Schneeman, Barbara O; Stang, Jamie; de Jesus, Janet; et al.
ABSTRACT: Background: Developing food-based dietary guidelines (FBDGs) for infants and toddlers is a complex task that few countries have attempted. Objectives: Our objectives are to describe the process of food pattern modeling (FPM) conducted to develop FBDGs for the Dietary Guidelines for Americans, 2020–2025 for infants 6 to <12 mo and toddlers 12 to <24 mo of age, as well as the implications of the results and areas needing further work. Methods: The US 2020 Dietary Guidelines Advisory Committee, with the support of federal staff, conducted FPM analyses using 5 steps: 1 ) identified energy intake targets; 2 ) established nutritional goals; 3 ) identified food groupings and expected amounts, using 3 options for the amount of energy from human milk in each age interval; 4 ) estimated expected nutrient intakes for each scenario, based on nutrient-dense representative foods; and 5 ) evaluated expected nutrient intakes against nutritional goals. Results: For human milk–fed infants (and toddlers), example combinations of complementary foods and beverages were developed that come close to meeting almost all nutrient recommendations if iron-fortified infant cereals are included at 6 to <12 mo of age. These combinations would also be suitable for formula-fed infants. For toddlers not fed human milk, 2 patterns were developed: the Healthy US-Style Pattern and the Healthy Vegetarian Pattern (a lacto-ovo vegetarian pattern). Achieving nutrient recommendations left virtually no remaining energy for added sugars. Conclusions: It is challenging to meet all nutrient needs during these age intervals. Added sugars should be avoided for infants and toddlers <2 y of age. Further work is needed to 1 ) establish a reference human milk composition profile, 2 ) update and strengthen the DRI values for these age groups, and 3 ) use optimization modeling, in combination with FPM, to identify combinations of foods that meet all nutritional goals.